As representações sociais sobre ensino superior de professores de graduação da área da saúde - Novikoff, Cristina (2006)
The present thesis deals with the graduation of the area of the health university professors social representations about higher education of private administrative category. Considering that the higher education of the private net, currently representing 88.9% of the IES, we understand that we would have to center our inquiry next to the university professors, looking for to understand the meanings that establish with this education. The disruption with the functions of this education is estimate that the external and internal norms printing values configured and configurantes in and of the social representations on higher education in the university professors, favoring. The consequences of these representations still little are present in studies and if they make necessary and important. It is questioned, as the university professors understand the functions of higher education? How they analyze higher education? That social representation comes constructing on this level of education? Moreover, considering the importance to analyze the possibilities of changes front the situations that these university professors are collated, our study look for to also investigate which the forms of valuation and confrontation (to collate and to face) that they come constructing in its daily one. The objective was to apprehend the social representations of higher education in the university professors of courses of actual graduation in the area of the health, being examined the description-social context and describing the nets of meanings and social support where the university professors anchor its knowledge, values and forms of confrontations. The research used as regarding theoretician the Theory of the Social Representations of Moscovici (1978), the concepts of values of Hessen (1980) and the concepts of confrontation of Leibovich and Cols (2002). The inquiry drawing was reference in Vasconcelos (2002), focus the interaction of the quantitative and qualitative boarding of the research. The applied methodology was diversifying, initiating itself by means of a daily pay-test (CZAJA & JOHNNY, 1996), and passing to the application of half-structuralized questionnaire and an inventory of valuation and confrontation (LEIBOVICH & COLS, 2002) the 79 university professors. The processing of analysis of the data had been carried through in the program excel and later with content analysis (BARDIN, 1977; FRANCO, 2003). Such procedures had allowed the creation of five categories of values contained in the investigated social representations, namely: social-relational values, normative values, identity values, cognizance-pedagogic values and social-professionals values. Two forms the valuation of higher education as being: challenge and threat. The confrontation strategies had centered in the emotion and of passive and preventive form. The analysis of the social representations of the university professors pointed a disruption of the function of superior education in the higher education institutions, as it came historic being praised